2023
DOI: 10.1039/d2ta08386h
|View full text |Cite
|
Sign up to set email alerts
|

Building a rigid-soft coupling interphase by a reduction–oxidation collaborative approach with lithium difluorobis(oxalato) phosphate additives

Abstract: Optimizing the properties of solid electrolyte interphase (SEI) layers on graphite electrodes is a crucial method for influencing the performance of cells. However, most studies ignore any potential synergistic effects...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…As reported, a stable SEI is established as a prerequisite for realizing the practical application of silicon-based anode cells. Thus, various types of electrolyte additives which are usually able to preferentially form stable SEI on the anode surface before the decomposition of electrolyte body are used in Si-based LIBs. , It is reported that additives of fluoroethylene carbonate (FEC), vinyl carbonate (VC), (pentafluoro­phenyl)­borane (TPFPB), lithium bis­(oxalate)­borate (LiBOB), and lithium difluorobisoxalate phosphate (LiDFBOP) have shown positive effects on improving the cycle life of Si-based anodes. FEC has once been considered as the most promising additive because its reduction products are mainly composed of polyolefins and LiF, and its derived SEI has characteristics of flexibility and high ionic conductivity. However, FEC will decompose at high temperature to generate gaseous products, especially HF, which is very destructive to cycling and safety performances .…”
Section: Introductionmentioning
confidence: 99%
“…As reported, a stable SEI is established as a prerequisite for realizing the practical application of silicon-based anode cells. Thus, various types of electrolyte additives which are usually able to preferentially form stable SEI on the anode surface before the decomposition of electrolyte body are used in Si-based LIBs. , It is reported that additives of fluoroethylene carbonate (FEC), vinyl carbonate (VC), (pentafluoro­phenyl)­borane (TPFPB), lithium bis­(oxalate)­borate (LiBOB), and lithium difluorobisoxalate phosphate (LiDFBOP) have shown positive effects on improving the cycle life of Si-based anodes. FEC has once been considered as the most promising additive because its reduction products are mainly composed of polyolefins and LiF, and its derived SEI has characteristics of flexibility and high ionic conductivity. However, FEC will decompose at high temperature to generate gaseous products, especially HF, which is very destructive to cycling and safety performances .…”
Section: Introductionmentioning
confidence: 99%
“…To further validate the benefits of the RF method, leakage current testing provides evidence of the performance advantages associated with the interface film formed via the RF method in terms of Li + conductivity. As shown in Figure c, the leakage current through RF (0.02481 mA) is lower than that through NF (0.03333 mA), indicating that the interface film generated using the RF method can mitigate the occurrence of side reactions on the electrode surface . The evolution of the CEI layer is further elucidated through EIS.…”
Section: Resultsmentioning
confidence: 94%
“…As shown in Figure 3c, the leakage current through RF (0.02481 mA) is lower than that through NF (0.03333 mA), indicating that the interface film generated using the RF method can mitigate the occurrence of side reactions on the electrode surface. 42 The evolution of the CEI layer is further elucidated through EIS. An LNMC622||Li battery was used to investigate the influence of different film-forming voltage scopes on the positive electrode interface, as shown in Figure 3d.…”
Section: Electrochemical Performances Of Lnmc622||limentioning
confidence: 99%